Oral Administration of Resveratrol-Loaded Solid Lipid Nanoparticle Improves Insulin Resistance Through Targeting Expression of SNARE Proteins in Adipose and Muscle Tissue in Rats with Type 2 Diabetes - Roohollah Mohseni; Zahra ArabSadeghabadi; Nasrin Ziamajidi; Roghayeh Abbasalipourkabir; Azam RezaeiFarimani (Nanoscale Research Letters, 2019)
Abstract In the current study, we developed resveratrol (RES)-loaded solid lipid nanoparticle (SLN-RES) in order to improve insulin resistance through the upregulation of SNARE protein complex in rats with type 2 diabetes. The SLN-RES characteristics include the following: the average size of 248 nm, the zeta potential of − 16.5 mV, and 79.9% RES entrapment efficiency. The release profile of SLN-RES showed an initial burst followed by a sustained release in natural condition. Infrared spectroscopy results revealed good incorporation of RES into core SLN. Spherical nanoparticle with less aggregation was observed under electronic microscopic examination. Oral administration of SLN-RES prevented weight loss and showed better hypoglycemic effect than RES. Serum oxidative stress status was restored to the normal level by SLN-RES. Furthermore, expression of synaptosomal-associated protein 23 (Snap23), syntaxin-4 (Stx4), and vesicle-associated membrane protein 2 (Vamp2) as the major elements of SNARE protein complex were reduced by SLN-RES more significantly than RES treatment in muscle tissue. However, SLN-RES has a similar effect to RES treatment in adipose tissue. Taken together, our results revealed SLN-RES could be a modern and interestingly therapeutic approach for the improvement of insulin resistance through targeting the expression of Snap23, Stx4, and Vamp2 in adipose and muscle tissues.